THE STUDY OF ORGANIZATION CULTURE AND LEADERSHIP: IMPROVING PERFORMANCE - Rakhmat Kabul, Eka; Mulyana, Mulyana; Limakrisna, Nandan (Dinasti Publisher, 2021)
This researches aims to analyze and prove the influence of of leadership, organizational culture, competence and teacher work motivation on teacher performance. The research method used in this research is descriptive survey method and explanatory survey with sample size of 225 respondents, and data analysis method used is SEM (Structural Equation Modeling). Based on the results of the research, then obtained the findings as follows Leadership, organizational culture, teacher competence, and work motivation simultanously have a positive and significant effect on teacher performance. Work motivation have dominant affects on teacher performance.